AB1088 The patients' viewpoint on a specialised biologic service. (15th June 2017) - Cefai, E; Balzan, D; Mercieca, C; Borg, AA
Abstract : Background: Biologic disease modifying anti-rheumatic drugs (DMARDs) have been a major breakthrough in the treatment of inflammatory arthritis. In clinical practice, providing timely monitoring to ensure continued efficacy and safety remains a challenge. The availability of a dedicated clinic for patients on biologics may help meet these standards. Objectives: The aim of this study was to get the patients' perspective of our dedicated biologic clinic and identify any unmet needs. Methods: Patients attending the biologic clinic between April and September 2016 and who were on a biologic for more than 2 years were interviewed by a trainee following their clinic visit. The patients were asked about their level of satisfaction on various aspects including waiting times, education, involvement in decision-making and duration of consultations. Results: 44 patients (23 females, 21 males) participated in the survey, of whom 21 suffered from rheumatoid arthritis, 17 from ankylosing spondylitis and 6 from psoriatic arthritis. The mean age of participants was 55.1 (SD 12.62) years. The mean DAS28 was 2.26 (SD 1.03) and the mean BASDAI was 4.21 (SD 2.4). Disease duration was less than 5 years in 20%, 6 to 10 years in 30% and more than 10 years in 50%. Overall satisfaction with arthritis education before initiation of treatment was 91%, which then dropped to 76% after treatment initiation. Satisfaction with education regarding biologic therapy was more consistent at 84% and 81% before and after starting treatment, respectively. 84% of patients reported to be satisfied with their involvement in the decision to start and continue biologic therapy. 77% of patients were satisfied with a consultation lasting 15 to 20 minutes and 77% were also satisfied with 6-monthly visits. The most valued source of education was communication with the caring rheumatologist (n=32), followed by specialist nurse education (n=15), Internet resources (n=14) and use of leaflets (n=13). 95% of patients reported to have rarely or never missed an appointment. The rheumatology advice line was used by 54% of patients, whilst the rest reported that they did not need it since starting the biologic. The greater majority of advice line users were very satisfied with the service provided. Amongst the unmet needs mentioned, were better arthritis education and the introduction of telephone consultations. Conclusions: Even though most patients were clinically well-controlled, continued education delivered by the caring rheumatologist and specialist nurse is still greatly valued. Patients attending this clinic highly valued the staff dedication and had good communication with their caring clinician. They were highly satisfied with the length and frequency of consultations. Nonetheless, a significant number suggested the need to introduce telephone consultations, which could be considered for those stable patients after receiving proper education. Disclosure of Interest: None declared